2018
DOI: 10.1016/j.jacc.2018.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Risk Prediction of Coronary Artery Disease in 480,000 Adults

Abstract: BackgroundCoronary artery disease (CAD) has substantial heritability and a polygenic architecture. However, the potential of genomic risk scores to help predict CAD outcomes has not been evaluated comprehensively, because available studies have involved limited genomic scope and limited sample sizes.ObjectivesThis study sought to construct a genomic risk score for CAD and to estimate its potential as a screening tool for primary prevention.MethodsUsing a meta-analytic approach to combine large-scale, genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
620
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 670 publications
(701 citation statements)
references
References 21 publications
20
620
3
4
Order By: Relevance
“…Our study substantiates the findings by Inouye et al () and Khera et al () showing that GPRS can boost individual risk prediction of common diseases. Here, we come to the conclusion, that at least for prediction of CAD status there is no need to use a sledge‐hammer to crack the nut.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study substantiates the findings by Inouye et al () and Khera et al () showing that GPRS can boost individual risk prediction of common diseases. Here, we come to the conclusion, that at least for prediction of CAD status there is no need to use a sledge‐hammer to crack the nut.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, a truly external validation in data generated with a different technology, at another time point, in a different population is required to evaluate the absolute classification performance of the models. Interestingly, this is the case also for other published GPRS by Khera et al () and Inouye et al ().…”
Section: Discussionsupporting
confidence: 79%
“…It has always been of clinical focus to foresee the risk of heart failure via genetic background characteristics. GRS was used to identify patients with Mendelian and complex disease patterns known as loci for HF risk factors, such as CAD, Cardiometabolic Disease, Blood Pressure and atrial fibrillation . Heart failure has similar or worse prognosis when compared to most cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic risk scores (GRS), which is the sum of risk genes in individuals has been beneficial to primary prevention. Genome‐wide association study (GWAS) studies have identified 73 gene mutation loci for coronary artery disease (CAD), and almost 100 genes were associated with cardiomyopathies (most of which are DCM and HCM), while only few previous studies such as studies on coronary artery disease, and cardiometabolic diseases in cardiovascular disease have shown the use of genomic information in risk prediction.…”
Section: Introductionmentioning
confidence: 99%
“…[67][68][69] This approach has been shown to predict risk in patients with FH. 67 A different approach is to use a very large number of SNPs with a lower threshold of statistical significance (49 310 SNPs in one study 70 ; 1.7 million in another 71 ). This has also been shown to be valid in patients with familial hypercholesterolaemia.…”
Section: Emergence Of Pcsk9 As a Rare Cause Of Fh: Discovery Of A Nmentioning
confidence: 99%